Combination Effect of Extracts and Pure Compounds of Endophytic Fungi Isolated from Sungkai (Peronema canescens) Leaves on Antioxidant Activity - Elfita; Oktiansyah, Rian; Mardiyanto; Setiawan, Arum; Widjajanti, Hary (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Endophytic fungi extracts have various biological and pharmacological activities as natural antioxidants which have the potential to be developed in the pharmaceutical. Drugs made from natural substances frequently work best when they are present in large quantities. This may result in unfavorable side effects from using more of one substance at a time. This limitation can be overcome by using a combination of the extracts/pure compounds that allow synergistic interactions with strong antioxidant properties at fairly low concentrations. The purpose of this research was to determine the combined effect of endophytic fungi extracts and its pure compounds on their antioxidant activity. This research was initiated by rejuvenating eight selected endophytic fungal isolates from Sungkai leaves and morphological characterization was carried out. Each fungus was cultivated in PDB medium for 4 weeks under statistical conditions. Ethyl acetate was used to extract the endophytic fungi’s liquid culture, which was then evaporated. Each endophytic fungal extract (PD1-PD8) and their five pure compounds were tested for antioxidant activity by the DPPH method. Then a combination of two and three extracts was carried out with a ratio of 1:1. The results show that the interaction of the mixture of endophytic fungi extracts and their pure compounds can be classified as synergistic (combined effect of the extracts > individual effects), additive (combined effect of the extracts = individual effect), and nothing is antagonistic (combined effect of the extracts < individual effects). The best combination in this study was PD4+PD5+PD6 (1:1:1) which could be used as a formula for further research into in vivo immunostimulant tests. Another conclusion from this research is that the pure compounds contained in the extracts have lower antioxidant activity than the extracts and do not have a synergistic effect on the combination.